Analysis of position-dependent cavity parameters in irradiated metals to obtain insight on fundamental defect migration phenomena☆. (February 2023) - Lin, Yan-Ru; Bhattacharya, Arunodaya; Zinkle, Steven J.
Graphical abstract: Highlights: Bubble formation was observed within the void-denuded zones, indicative of a small bubble-denuded zone compared to the void-denuded zone. Enhanced cavity swelling regions adjacent to void-denuded zones were observed by planar sinks in samples with moderate sink strengths. The temperature dependence of the cavity-denuded zone could be used to quantitatively estimate defect (vacancy and He-vacancy complex) migration energies. Radiation-enhanced diffusion together with thermal diffusion can broaden the implanted ion profile and reduce the midrange safe analysis region. Sufficiently high ion energies are generally needed to provide an adequate safe analysis region for heavy ion irradiation effects studies. Abstract: Motion of point defects is a fundamental process that governs microstructure and properties of materials. Here, we examine the near-surface and grain boundary cavity swelling depth profiles in neutron- and ion-irradiated simple metals (Cu, Ni, and Fe-Cr) and investigate diffusional broadening of implanted Ni ions in Fe-Cr alloys. Vacancy migration energies and radiation-enhanced diffusion were experimentally estimated. Cavity denuded zone widths near planar sinks are shown to be dependent on temperature, damage rate, balance of point defects and sinks, and vacancy migration energies. An enhanced cavity swelling zone adjacent to the void-denuded zone was observed in specimens with low to moderate sink strength and interpreted as evidence of 1D gliding interstitial clusters. Radiation-enhanced diffusional broadening of implanted Ni ions (at 400–550 °C) in Fe and Fe-Cr was up to 250 nm toward the surface, which leads to a much broader near-peak-damage region where cavity swelling is suppressed. Diffusional broadening of implanted ions is calculated to be similarly pronounced for self-ion irradiations, particularly near the peak and higher swelling temperature regimes. Adequately high ion energies (∼8–15 MeV) are recommended for ion-irradiation studies to provide a sufficiently broad midrange safe analysis region with minimized surface and injected ion effects.